Analisis Efisiensi Teknis Usahatani Padi di Kabupaten/Kota Jawa Timur Tahun 2020 - Soleh Hanafi Ihsan; Mohtar Rasyid; Dyah Wahyuningsih (Program Studi Ilmu Ekonomi UIN Sunan Ampel Surabaya, 2021)
The purpose of this study is to determine the level of technical efficiency of rice farming in East Java districts/cities in 2019-2020. The results show that there are 27 regencies/cities or around 71.05 percent of the total, while in this study there are 11 regencies/cities or about 28.94 percent of the inefficient rice farms that have been efficient in using inputs. The results of the analysis show that rice farming in districts/cities in East Java is in a position to increase its return to scale, which is in a position where the increase in output is greater than the increase in inputs.